CORRECTION OF SOME SIDE EFFECTS TO ANTI-TUBERCULOSIS THERAPY IN MODERN CONDITIONS - Yu.V. Prosvetov; A.Yu. Gusarova; S.S. Barinov; A.V. Husarova (Сучасні медичні технології)
Introduction. Tuberculosis has not been eradicated in any country in the world. Chemotherapy plays a leading role in this fight. In the last two decades, the level of chemoresistant tuberculosis has increased significantly, contributing to an increase in the total number of side effects, often severe and widespread.